Failed Sisterhood: Expectations and Betrayal Between the Women of the Antebellum South - Filidoro, Erica (My University, 2008)
Mistresses and slave women in the antebellum South lived and often suffered together under an oppressive patriarchy. They all endured a kind of enslavement in a system that reduced all women to the property of White men in some way. Previous historians have argued that this kindled gender solidarity between White and Black women. Others have argued that issues of race, class, privilege, and jealousy prevented the formation of any sense of sisterhood between the two groups of women. However, the issue is more complex than simply discovering whether there was or was not gender solidarity. Although antebellum women did not achieve any real unity, mistress journals and slave narratives reveal that on rare but important occasions they acknowledged the possibility of sisterhood and responded with guilt, betrayal, or anger at their failure to achieve it. These subtler nuances reveal a complicated relationship between mistress and bondswoman under slavery that transcended easy definitions according to race, privilege, or gender.
Oshkosh Scholar, Volume 3, 2008, pp. 34-43.
Keywords: Black Women; Slaves--United States; African-American women; Women slaves -- America-- history; Race relations; Sisterhood; Antebellum South; Southern women